Bond-forming and electron-transfer reactivity between Ar2+ and N2. Issue 19 (6th May 2021) - Armenta Butt, Sam; Price, Stephen D.
Abstract : Electron transfer between Ar 2+ and N2 involves both complexation and direct dynamics; a stripping-style pathway generates ArN + . Abstract : Collisions between Ar 2+ and N2 have been studied using a coincidence technique at a centre-of-mass (CM) collision energy of 5.1 eV. Four reaction channels generating pairs of monocations are observed: Ar + + N2 +, Ar + + N +, ArN + + N + and N + + N + . The formation of Ar + + N2 + is the most intense channel, displaying forward scattering but with a marked tail to higher scattering angles. This scattering, and other dynamics data, is indicative of direct electron transfer competing with a 'sticky' collision between the Ar 2+ and N2 reactants. Here Ar + is generated in its ground ( 2 P) state and N2 + is primarily in the low vibrational levels of the C 2 Σu + state. A minor channel involving the initial population of higher energy N2 + states, lying above the dissociation asymptote to N + + N, which fluoresce to stable states of N2 + is also identified. The formation of Ar + + N + by dissociative single electron transfer again reveals the involvement of two different pathways for the initial electron transfer (direct or complexation). This reaction pathway predominantly involves excited states of Ar 2+ ( 1 D and 1 S) populating N2 + * in its dissociative C 2 Σu +, 2 2 Πg and D 2 Πg states. Formation of ArN + + N + proceeds via a direct mechanism. The ArN + is formed, with significant vibrational excitation, in its ground (X 3 Σ − ) state. Formation of N + + N + is also observed as a consequence of double electron transfer forming N2 2+ . The exoergicity of the subsequent N2 2+ dissociation reveals the population of the A 1 Πu and D 3 Πg dication states.